Decoupling silicon metabolism from carbon and nitrogen assimilation poises diatoms to exploit episodic nutrient pulses in a coastal upwelling system - Maniscalco, Michael A.; Brzezinski, Mark A.; Krause, Jeffrey W.; Thamatrakoln, Kimberlee (Frontiers in Marine Science, 2023)
Diatoms serve as the major link between the marine carbon (C) and silicon (Si) biogeochemical cycles through their contributions to primary productivity and requirement for Si during cell wall formation. Although several culture-based studies have investigated the molecular response of diatoms to Si and nitrogen (N) starvation and replenishment, diatom silicon metabolism has been understudied in natural populations. A series of deckboard Si-amendment incubations were conducted using surface water collected in the California Upwelling Zone near Monterey Bay. Steep concentration gradients in macronutrients in the surface ocean coupled with substantial N and Si utilization led to communities with distinctly different macronutrient states: replete ('healthy'), low N ('N-stressed'), and low N and Si ('N-and Si-stressed'). Biogeochemical measurements of Si uptake combined with metatranscriptomic analysis of communities incubated with and without added Si were used to explore the underlying molecular response of diatom communities to different macronutrient availability. Metatranscriptomic analysis revealed that N-stressed communities exhibited dynamic shifts in N and C transcriptional patterns suggestive of compromised metabolism. Expression patterns in communities experiencing both N and Si stress imply that the presence of Si stress may partially ameliorate N stress and dampen the impact on organic matter metabolism. This response builds upon previous observations that the regulation of C and N metabolism is decoupled from Si limitation status, where Si stress allows the cell to optimize the metabolic machinery necessary to respond to episodic pulses of nutrients. Several well-characterized Si-metabolism associated genes were found to be poor molecular markers of Si physiological status; however, several uncharacterized Si-responsive genes were revealed to be potential indicators of Si stress or silica production.